The Art of Forgetting : Disgrace and Oblivion in Roman Political Culture - Flower, Harriet I. (Book collections on Project MUSE., 2006)
Elite Romans periodically chose to limit or destroy the memory of a leading citizen who was deemed an unworthy member of the community. Sanctions against memory could lead to the removal or mutilation of portraits and public inscriptions. The author of this book provides the first chronological overview of the development of this Roman practice - an instruction to forget - from archaic times into the second century A.D. She explores Roman memory sanctions against the background of Greek and Hellenistic cultural influence and in the context of the wider Mediterranean world.